저시력 시각장애인의 키오스크 사용성 평가 연구 - 김경훈; 김유미; 백수민; 고정현; Kyounghoon Kim; Yumi Kim; Sumin Baeck; Jeong Hyeun Ko (Chŏngbo Kwalli Hakhoechi, 2024)
In the rapid digital transformation era, kiosks have become a common element in daily life. However, their widespread deployment has introduced new challenges for socially marginalized groups, including individuals with disabilities and the elderly. This study aims to evaluate the usability of kiosks for individuals with low vision and propose improvement strategies. The study was conducted with eight low-vision university students from A University in Gyeongsangbuk-do and four non-disabled university students from Daegu. Usability was assessed through experiments involving a self-service certificate issuance kiosk and a fast-food restaurant kiosk, using Jakob Nielsen's five usability evaluation criteria: learnability, efficiency, memorability, error prevention, and satisfaction. The results revealed that individuals with low vision faced significant difficulties with small text size, low contrast, no physical buttons, and lack of screen zoom functionality. To address these issues, the study recommends enhancements such as increasing text size and contrast, incorporating physical buttons, adding zoom functionality, ensuring consistent UI design, and providing auditory feedback. This study provides foundational data for enhancing information accessibility for individuals with low vision. It offers critical insights into kiosk design and policy recommendations, thereby contributing to the mitigation of the digital divide. 급격한 디지털 전환의 흐름 속에서 키오스크는 일상에서 흔히 접하는 기기로 자리 잡고 있다. 그러나 키오스크의 급격한 확산은 장애인과 고령자 등 사회적 약자에게 새로운 문제를 야기하고 있다. 본 연구는 저시력 시각장애인의 키오스크 사용성을 평가하고 이를 개선하기 위한 방안을 제시하는 데 목적이 있다. 본 연구는 경상북도에 소재한 A 대학교의 저시력 시각장애인 대학생 8명과 대구 지역 비장애인 대학생 4명을 대상으로 진행되었다. 무인 증명서 발급기와 패스트푸드점 키오스크를 이용하는 실험을 통해 제이콥 닐슨의 5가지 사용성 평가 기준(학습용이성, 효율성, 기억용이성, 오류방지성, 만족도)을 바탕으로 사용성을 평가하였다. 연구 결과, 저시력 시각장애인은 키오스크 사용 시 작은 글자 크기, 낮은 명도 대비, 물리적 버튼 부재, 화면 확대/축소 기능 부족 등으로 많은 어려움을 겪고 있었다. 이를 개선하기 위해 글자 크기 및 명도 대비 개선, 물리적 버튼 도입, 화면 확대/축소 기능 추가, 일관된 UI 디자인 유지, 음성 피드백 제공 등의 방안이 필요하다. 본 연구는 저시력 시각장애인의 정보 접근성을 향상하기 위한 기초자료로 활용될 수 있으며, 키오스크 설계 및 정책적 제언을 위한 중요한 근거를 제공하여 디지털 격차 해소에 기여할 수 있을 것이다.